2D GeP: An Unexploited Low‐Symmetry Semiconductor with Strong In‐Plane Anisotropy. Issue 14 (26th February 2018) - Li, Liang; Wang, Weike; Gong, Penglai; Zhu, Xiangde; Deng, Bei; Shi, Xingqiang; Gao, Guoying; Li, Huiqiao; Zhai, Tianyou
Abstract: Germanium phosphide (GeP), a new member of the Group IV–Group V compounds, is introduced into the fast growing 2D family with experimental and theoretical demonstration of strong anisotropic physical properties. The indirect band gap of GeP can be drastically tuned from 1.68 eV for monolayer to 0.51 eV for bulk, with highly anisotropic dispersions of band structures. Thin GeP shows strong anisotropy of phonon vibrations. Moreover, photodetectors based on GeP flakes show highly anisotropic behavior with anisotropic factors of 1.52 and 1.83 for conductance and photoresponsivity, respectively. This work lays the foundation and ignites future research interests in Group IV–Group V compound 2D materials. Abstract : A new in‐plane anisotropic 2D material GeP with a tunable bandgap is introduced. Angle‐resolved polarized Raman investigations indicate that the GeP flake has a strong anisotropic Raman response. Moreover, a remarkable in‐plane anisotropic conductance with the anisotropic factor of 1.52 and an in‐plane anisotropic photoresponsivity with an anisotropic factor of 1.83 are realized in GeP flakes.